Implementasi Kebijakan Retribusi Parkir di Kota Pekanbaru (Studi Kasus di UPT Perparkiran Kota Pekanbaru) - Rahmi, Anjel Dinia; Febrian, Ranggi Ade (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study is to determine the Implementation of Parking Retribution Policy in Pekanbaru City (Case Study in UPT Parking Pekanbaru City). Policy Implementation Indicators include: Communication, Resources, Disposition and Bureaucratic Structure. The type of research used Qualitative research method, Key Informant Head of Pekanbaru City Transportation Agency, Informant Head of Parking Control and Operations Division, Head of UPT Parking Pekanbaru City, Operational Staff of UPT Parking, Official Parking Attendants (Jl Sudirman, Jl Subrantas and Jl Soekarno Hatta) and Parking User Community. Sampling for Parking User Community using Purposive Sampling. The types and techniques of data collection used consist of primary data collected using interview techniques, and secondary data collected using observation techniques. Data analysis consists of four simultaneous activity flows, namely, Data collection, data reduction, data presentation, drawing conclusions/verification. Research Results on the Implementation of Parking Retribution Policy, The implementation of the parking retribution policy in Pekanbaru City which is carried out by the Parking UPT has been running, but has not been fully optimal. This can be seen from: There is still a discrepancy between the rates collected by parking attendants and the official rates set in Perwako No. 2 of 2025. Need to Increase Commitment and Discipline of Parking Attendants Provide routine coaching and discipline to parking attendants. Provide an understanding that parking is a public service, not just a target for deposits